A systematic interpretation of the quantum cutting effect by a cooperative energy transfer mechanism in Te4+/Yb3+ co-doped tellurite glasses - Rufino Souza, Ana Kely; Silva, Junior Reis; Costa, Francine Bettio [UNESP]; Silos Moraes, Joao Carlos [UNESP]; Oliveira Nunes, Luiz Antonio de; Cunha Andrade, Luis Humberto da; Lima, Sandro Marcio (Elsevier, 2023)
The near-infrared downconversion (DC) mechanism in Te4+/Yb3+ co-doped 75TeO2–25Li2O tellurite glasses (amounts in mol%) was closely followed using optical and thermal spectroscopy techniques. The glasses were prepared by the conventional melt-quenching method, with a melting temperature of 800 °C, in an ambient atmosphere, which were the best synthesis conditions for observing Te4+ in the glass. The results indicated that excitation in the ultraviolet region led to an intense emission of two NIR photons (at around 978 nm) in the co-doped tellurite glasses. This effect revealed the occurrence of a cooperative energy transfer (CET) mechanism in the system, where a Te4+ ion was responsible for the excitation of two Yb3+ ions. The CET efficiency (ηCET) was calculated from the Te4+ lifetime, obtaining a maximum of 74% for the tellurite glass prepared with the highest Yb3+ concentration. The use of thermal lens spectroscopy confirmed the quantum cutting effect, by observing the dependence of the thermal properties of the glass on the Yb3+ concentration. A maximum DC efficiency of 137% was measured for the sample with 4 mol% of Yb3+.
Keywords: Cooperative energy transfer; Downconversion; Fluorescence quantum efficiency; Quantum cutting; Te4+ ion; Tellurite glass; Thermal lens spectroscopy; Yb3+ ion